Taste-masking methods in multiparticulate dosage forms with a focus on poorly soluble drugs - Simšič Tilen; Planinšek Odon; Baumgartner Ana (Acta Pharmaceutica)
In the past, the administration of medicines for children mainly involved changes to adult dosage forms, such as crushing tablets or opening capsules. However, these methods often led to inconsistent dosing, resulting in under- or overdosing. To address this problem and promote adherence, numerous initiatives, and regulatory frameworks have been developed to develop more child-friendly dosage forms. In recent years, multiparticulate dosage forms such as mini-tablets, pellets, and granules have gained popularity. However, a major challenge that persists is effectively masking the bitter taste of drugs in such formulations. This review therefore provides a brief overview of the current state of the art in taste masking techniques, with a particular focus on taste masking by film coating. Methods for evaluating the effectiveness of taste masking are also discussed and commented on. Another important issue that arises frequently in this area is achieving sufficient dissolution of poorly water-soluble drugs. Since the simultaneous combination of sufficient dissolution and taste masking is particularly challenging, the second objective of this review is to provide a critical summary of studies dealing with multiparticulate formulations that are tackling both of these issues.